ETUDE CRITIQUE DU MOUVEMENT DES RECETTES NON FISCALES MOBILISEES DANS UNE REGIE FINANCIERE. CAS DE LA DGRAD RESSORT DU HAUT-UELE - ODIBOBI, Chadrack ATIGADA (IJRDO - Journal of Business Management, 2022)
This study focuses on the critical analysis of the mouvement of non-tax revenues mobilized in a financial authority.  Case of the DGRAD emerges from Haut-Uélé. At the end of the investigation, the results obtained show that there is a very low level of execution of the assignments of non-tax revenues collected at the DGRAD in  2016. In 2015, on the other hand, it slightly exceeded half of the assignments. In addition, over the last three years of study, the level of execution is less than 50%, i.e. 1.96% in 2016, 20.42% in 2017 and 32.67% in 2018, this decrease in the rate of  The execution sufficiently demonstrates this weakness in the evolution of non-tax revenues.  On the other hand, over the entire period of the study, the rate amounted to 27.94% so during the four years under review, the DGRAD Ressort du Haut-Uele only generated capital losses,  which led to negative differences over the entire period of the study.  Another factor that explains the weakness of this development is the effort made by this financial authority.  Thus, it emerges that in 2015, there was a mobilization effort of 50.7%;  in 2016, its rate fell to 1.8%;  in 2017, the effort made represented only 18.3% and in 2018, the effort made was 29.2%.  To do this, the year 2015 being a base year, remains the one that DGRAD Haut-Uélé has mobilized considerable energy from non-tax revenues.  On the other hand, the other years show a weakness in the efforts of non-tax revenues.  In view of all that has just preceded, several constraints which plague the maximization of non-tax revenues are raised in particular the weakness of the Congolese tax system, the unsuitability of this system because of problems linked to taxation, the lack of  ethics, the systematic reduction of the tax base, documentary fraud, neglect of the human factor, the problem of non-tax revenue collection, tax evasion and corruption. In view of the constraints raised previously, several strategies are possible in order to maximize non-tax revenues and actively participate in the bailout of the State fund in this case: the documentation of this financial authority, the capacity building of its agents,  reduce fraud and corruption, raise awareness among taxable persons, take into account the human factor, reform the procedure relating to the basis, control and methods of collecting non-tax revenue.